Penagruh Price Earning Ratio (PER) dan Price To Book Value (PBV) Terhadap Return On Assets (ROA) Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia - Della Maretha (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aimed to examine the effect of Price Earning Ratio (PER) and Price To Book Value (PBV) of the Return on Assets (ROA), the LQ45companies listed in Indonesia Stock Exchange by using multiple linear regression analysis. One of the requirements to test multiple linear regression analysis is to test the classical assumption. It is in need so that the regression equation which is derived is BLUE (Best Linear Unbiased Estimator). In addition to assessing the goodness of fitsuatu models the coefficients of determination test, F test and t test. This studyuses annual data from 2010 to 2013 for each study variabel. The result of this study indicate that the variabel Price Earning Ratio (PER) and Price to Book Value (PBV) jointly / simultaneous significant effect on Return on Assets (ROA), the Adjusted R2 value of 0.83877. this means that 83.88% Return on Assets (ROA) can be explained by the independent variables. While the remaining 16.12 % is influenced by other variables outside of research. Partially shows that Price Earning Ratio (PER) significant and positive impact on the Return on Assets (ROA), the value of t-statistic probability of 4.609170 and 0.0000. Price to Book Value (PBV) significant and positive impact on the Return on Assets (ROA), the value of t-statistic probability of 3.340151 and 0.0014. Keywords : Price Earning Ratio (PER), Price to Book Value (PBV), Return on Assets (ROA)